»There is something wrong with my child«: Benigne soft tissue tumors during childhood. Clinical questions – sonographic answers? »Mein Kind hat da was«: Benigne Raumforderungen der Weichteile im Kindesalter - Jüngert, Jörg (Chirurgische Praxis, 2023)
The differential diagnoses of tumors of the soft tissues in children and adolescents are manifold. Semimalignant and malignant causes must always be excluded, such as myofibromatosis, rhabdomyosarcoma, synovial sarcoma, fibrosarcoma, Ewing‘s sarcoma, osteosarcoma, chondrosarcoma, giant cell tumor, liposarcoma, metastases (e.g. neuroblastoma, lymphomas, acute lymphatic leukemia, etc.) or tumors originating from other organs (Abb. 14). High-resolution sonography can make a significant contribution to the classification of unclear findings. Especially benign lesions, which do not require immediate therapy, can be monitored sonographically in an excellent way. The high-end ultrasound equipment that is available in well equipped centres enables increasingly good assessments and diagnoses. At the same time, in addition to the expertise of the examiner, interdisciplinary cooperations with oncology, pediatric radiology, pediatric surgery, possibly plastic surgery, pathology and other disciplines are fundamental. However, the primary classification in the pediatric practice is decisive. The patient’s medical history, findings, clinic and maybe a first sonography form the basis for a specific question that can be addressed by a further sonografic centre. In case of suspicious findings, the sonographic examination should be extended to other organs in order to detect systemic diseases as far as possible. Depending on the plausibility of the working hypothesis and the suspected diagnosis, the indication for further imaging, histological clarification, therapy to be initiated or a wait- and-see attitude with follow-up examinations is given. In diagnostic imaging, sonography plays a leading and central role in the clarification of soft tissue findings and should be used as the first imaging procedure.
CRIS-Team Scopus Importer:2023-10-20
Keywords: nodules; soft tissue; swelling; tumor; ultrasound